1995
DOI: 10.1089/acm.1995.1.361
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Several Strains of Influenza Virus in Vitro and Reduction of Symptoms by an Elderberry Extract (Sambucus nigra L.) during an Outbreak of Influenza B Panama

Abstract: A standardized elderberry extract, Sambucol (SAM), reduced hemagglutination and inhibited replication of human influenza viruses type A/Shangdong 9/93 (H3N2), A/Beijing 32/92 (H3N2), A/Texas 36/91 (H1N1), A/Singapore 6/86 (H1N1), type B/Panama 45/90, B/Yamagata 16/88, B/Ann Arbor 1/86, and of animal strains from Northern European swine and turkeys, A/Sw/Ger 2/81, A/Tur/Ger 3/91, and A/Sw/Ger 8533/91 in Madin-Darby canine kidney cells. A placebo-controlled, double blind study was carried out on a group of indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
123
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(136 citation statements)
references
References 19 publications
1
123
1
3
Order By: Relevance
“…Judging from the pharmacological and clinical effects of elderberry reported by Vlachojyannis et al, 3) almost all the effects of elderberry warrant further investigation. Several in vitro studies on the anti-IFV activity of elderberry have found the inhibition of both haemagglutination 4) and viral proliferation, 24) and prevention of the adhesion of the virus to the host cell receptors. 14) In addition, elderberry has been reported to stimulate the immune system by enhancing the production of cytokines by monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Judging from the pharmacological and clinical effects of elderberry reported by Vlachojyannis et al, 3) almost all the effects of elderberry warrant further investigation. Several in vitro studies on the anti-IFV activity of elderberry have found the inhibition of both haemagglutination 4) and viral proliferation, 24) and prevention of the adhesion of the virus to the host cell receptors. 14) In addition, elderberry has been reported to stimulate the immune system by enhancing the production of cytokines by monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The elderberry has been traditionally used in the treatment of influenza, common cold infections, diabetes, and other ailments. [1][2][3] Although several clinical trials have shown that such symptoms as fever and sneezing derived from influenza were rapidly recovered from by treating with elderberry juice or its concentrated syrup, 4,5) its main components and the mechanism for its anti-IFV action have been not fully understood. Elderberry is known to be rich in phenolic compounds, including phenolic acid, flavonoids, catechins, and proanthocyanidins.…”
mentioning
confidence: 99%
“…Additionally, N. sativa compound extracts, especially its saponins, alkaloids, and flavonols, show similarities with known antiviral chemicals [38][39][40]. Finally, S. nigra extract has successfully inhibited influenza A and B viruses in vitro and in vivo [41]. S. nigra extracts are also characterized by a high content of antiviral flavonoid anthocyanins [42].…”
Section: Introductionmentioning
confidence: 99%
“…malic, citric, shikimic, fumaric, malonic, valeric acids), sugars, pectins and vitamins C and B (Dawidowicz et al, 2006;Veberic et al, 2009). Elderberries have antibacterial, antifungal, anti-inflammatory, antiviral and pro-immunological properties (Zakay-Rones et al, 1995;Netzel et al, 2005). Fresh fruits are rarely consumed and they are most commonly processed into syrups and jams.…”
Section: Introductionmentioning
confidence: 99%